Analyzing student performance in secondary education examination using logistic regressions - Acharya, Krishna Prasad (Management Dynamics, 2020)
The performance of the school examination results (CGPA) of 533 students who were admitted to higher secondary school in management stream of 2073 in Dolakha district was analyzed by examining their cumulative grade point average (CGPA) using binary logistic regression model. Factors affecting the CGPA were investigated. The factor that significantly influenced the CGPA in Secondary Education Examination (SEE) was types of schools. Other factors including gender and teaching language were found to be statistically not significant.